Influence of vertical internals on a bubbling fluidized bed characterized by X-ray tomography. (October 2015) - Maurer, Simon; Wagner, Evert C.; van Ommen, J. Ruud; Schildhauer, Tilman J.; Teske, Sinan L.; Biollaz, Serge M.A.; Wokaun, Alexander; Mudde, Robert F.
Highlights: Bubble rise velocity of a single bubble independent from size in a swarm of bubbles. Dependency between mean bubble size and mean rise velocity confirmed. X-ray analysis of different bubble properties with and without vertical internals. Significant reduction of the bubble size with vertical internals. Sharpening of the bubble size distribution with vertical internals. Abstract: An ultra-fast X-ray tomographic scanner is applied to study the hydrodynamics in a bubbling fluidized bed with and without vertical internals (e.g., heat exchanger tubes). The objective of this study is to understand the influence of vertical internals on hydrodynamic properties such as bubble volume, size and velocity and to provide measurement data for the design and scale-up of catalytic bubbling fluidized bed reactors with vertical internals. With these new measurements, correlations of bubble properties can be developed to reliably scale-up bubbling fluidized beds with vertical internals. For the investigated reactor with Geldart A/B particles, no relation between bubble size and velocity was observed for individual bubbles, i.e.; smaller bubbles tend to rise with higher velocities. A significant reduction in bubble size and sharpening of the bubble size distribution was generally obtained for a bed with vertical internals.